Quality of refrigerated oil-coated quail eggs during subsequent ambient storage - Singh, R P; Verma, S S (The Indian Journal of Animal Sciences, 2012)
Changes in the internal and sensory quality of quail eggs coated by ,praying or dipping in groundnut oil mixed with 200 ppm butylated hydroxytoulene were evaluated under ambient (24±2°C ; 57-58% RH) storage, following 30 days or refrigeration (5± 1 °C; 80-85% RH). The cumulative loss in the weight of oiled eggs was 2.5 to 2.6% only as against 8.3% in unoiled eggs after 15 days of ambient storage. Both the oiling treatments appeared almost equally effective in retarding  the decline in internal and sensory quality of eggs. However, no significant increase in thiobarbituric acid value was found during storage regardless of treatments. Unoiled and oiled eggs held under refrigeration for a month should be marketed within 5 and 15 days, respectively, under ambient condition.